Sistem Informasi Pengajuan Dana Fakultas Berorientasi Industri 5.0 Untuk Meningkatkan Akuntabilitas Keuangan - Sukmanasari, Putri Swastika; Marsono, Marsono; Alqodri, Febrianto; Triono, Alfiansyah Putra Pertama (METIK JURNAL, 2024)
This study aims to develop and implement the SISPEDA Application (Fund Submission Information System) as a basis for routine Work Down Payment (UMK) submissions and activities at the Faculty of Engineering, State University of Malang, with a focus on increasing financial accountability and transparency in the context of the Industrial Revolution 5.0. This study uses the System Development Life Cycle (SDLC) methodology consisting of planning, analysis, design, development, testing, implementation, and maintenance stages. Primary data were collected through interviews and observations of potential users, namely administrative staff and lecturers at the Faculty of Engineering, State University of Malang. The results of the unit testing trial, SISPEDA can run 100% so it is suitable for use. The results of the study indicate that the implementation of SISPEDA has succeeded in increasing the efficiency of the fund submission process by significantly reducing the time required. Overall, this study concludes that SISPEDA makes a positive contribution to improving financial governance at the Faculty of Engineering, State University of Malang and can be used as a model for the development of fund management information systems in other higher education institutions.